Macroporous Composite Cryogels with Embedded Polystyrene Divinylbenzene Microparticles for the Adsorption of Toxic Metabolites from Blood - Tanja Eichhorn; Alexander E. Ivanov; Maria B. Dainiak; André Leistner; Ingrid Linsberger; Hans Jungvid; Sergey V. Mikhalovsky; Viktoria Weber (Journal of Chemistry)
Composite monolithic adsorbents were prepared by the incorporation of neutral polystyrene divinylbenzene (PS-DVB) microparticles into macroporous polymer structures produced by cryogelation of agarose or poly(vinyl alcohol). The composite materials exhibited excellent flow-through properties. Scanning electron microscopy of the composite cryogels revealed that the microparticles were covered by thin films of poly(vinyl alcohol) or agarose and thus were withheld in the monolith structure. Plain PS-DVB microparticles showed efficient adsorption of albumin-bound toxins related to liver failure (bilirubin and cholic acid) and of cytokines (tumor necrosis factor-alpha and interleukin-6). The rates of adsorption and the amount of adsorbed factors were lower for the embedded microparticles as compared to the parent PS-DVB microparticles, indicating the importance of the accessibility of the adsorbent pores. Still, the macroporous composite materials showed efficient adsorption of albumin-bound toxins related to liver failure as well as efficient binding of cytokines, combined with good blood compatibility. Thus, the incorporation of microparticles into macroporous polymer structures may provide an option for the development of adsorption modules for extracorporeal blood purification.